KAJIAN KEMURNIAN DAN PENGARUH NISBAH PEREAKSI, pH AWAL REAKSI DAN SUHU REAKSI TERHADAP NILAI CMC & HLB NATRIUM LIGNOSULFONAT - Eric Wirtanto, Michael Lim, Zuhrina Masyithah (Jurnal Teknik Kimia USU, 2012)
Sodium lignosulphonate (SLS) is a product of isolated lignin sulphonation process using NaHSO3 as sulphonation agent.The research begins with isolated lignin from palm shell amd continued with sulphonation with mass ratio of palm shell lignin – NaHSO3(b/b) of 1:0.2, 1:0.3, and 1:0.5 and initial pH of 6, 7, and 8  at temperature 85 oC and 95 oC. The purity of SLS made in this studies was 66,782 %. The CMC value of this SLS ranged from 0,014 – 0,052; while the lowering of surface tension of water ranged from 53,63 – 59,83 dyne/cm.  The HLB value ranged from 3,805 – 4,278; means that this surfactant classified as lipophilic. The resulted SLS was dark brown, and water soluble.Keywords: palm shell lignin, lignin, sodium lignosulphonate, sulphonation